Perlindungan Hukum terhadap Korban Tindak Pidana Perdagangan Anak Perspektif Hak Asasi Manusia - Sulistya Eviningrum; Fitri Nur Sukmawati; Tri Anggis Hastari; Fayza Ilhafa (Ahmad Dahlan Legal Perspective, 2023)
This research was conducted to analyze the legal protection provided to child victims of child trafficking in Indonesia from a human rights perspective. The urgency of law enforcement is not only to tackle the crime of child trafficking but also to protect children who are victims of criminal acts. Children need protection from the fact that they have become victims. Not only physical protection, but mental and spiritual protection and social rehabilitation. The normative legal research method is used in this research, with the results of the research explaining: first, human rights and legal protection efforts against child victims of child trafficking are regulated and guaranteed in the Indonesian national legislative system based on the 1945 Constitutional Amendment, Human Rights Law Number 9 of 1999, Law No. 35 of 2014 concerning Child Protection, Law No. 21 of 2007 concerning the Elimination of Child Trafficking. One of the legal protection efforts is prevention, replacement, compensation, rehabilitation and integration. Efforts to protect child victims of trafficking: first, by providing rights to victims is the duty and responsibility of the state; second, the government works to ensure increased efforts to protect victims of trafficking. Carry out prevention and eradication activities to take action to prevent and overcome the crime of child trafficking. Encourage the establishment and/or improvement of legislation relating to child trafficking.